Twenty Years of Social Struggles: Notes for Future Research - Almeida, Lúcio Flávio Rodrigues de (Pontifícia Universidade Católica de São Paulo, 2016)
This is a preliminary review of some important social struggles that occurred in the 1996-2016 period, some of which continue today. Since this period coincides with the existence of the journal Social Struggles, with its explicitly engaged production of critical knowledge, I will make recourse mainly to this publication. The article is divided into three parts: 1) analysis of the new international context that soon became evident during this period; 2) an attempt to classify the struggles that emerged; 3) brief references to some of those struggles.